Study the Structural and Optical Properties of Pure Cadmium Sulfide Films by Thermal Vaporization Method - Abbas Ali Layij, Hussein Ali Noor (International Journal of Advanced Science and Technology, 2020)
Thin films of pure Cds were prepared with different thicknesses (100-200-300) nm by thermal vaporization into the vacuum, and the melting temperature of cds was (980) C° and evaporated at (900) c°. Through the study of X-ray diffraction, the films with a multi-crystalline nanostructure with a hexagonal phase appeared, and the preferred direction for growth is (002). The granular size of the prepared films was calculated and it was found that the granular size increases with increasing thickness and the average granular size of the thickness (100-200-300) nm were (18.71-23.31-29.10) nm respectively. Moreover, upon diagnosis by the atomic force microscope, the process of increasing the thickness resulted in a decrease in roughness the surface and the mean square root (Sqrt). The topography of the surface was studied through the scanning electron microscope. It was found that the films have a uniform distribution, and the optical properties were studied by recording both the absorbance and permeability spectrum for the wavelengths range of (300-1100) nm. In addition, the absorption coefficient and energy gap were calculated wherever it was decreased with the increase of the thickness at (2.6 - 2.43) eV.